On greedy approximation algorithm for the minimum resolving dominating set problem - Zhong, Hao (Journal of combinatorial optimization, 2024)
In this paper, we investigate the minimum resolving dominating set problem which is a emerging combinatorial optimization problem in general graphs. We prove that the resolving dominating set problem is NP-hard and propose a greedy algorithm with an approximation ratio of ( 1 + 2 ln n ) by establishing a submodular potential function, where n is the node number of the input graph.